ASSESSMENT OF SURFACE WATER RESOURCES FOR IRRIGATION PURPOSES IN ASSIUT GOVERNORATE, UPPER EGYPT - Morsi, Mamdouh Salama; Farrag, Abdel Hai. A.; Sayed, Esam E. A. El; Elewa, Ashraf M. T. (International Journal of Research -GRANTHAALAYAH, 2020)
Water from some sources may contain so much salt that it is unsuitable for irrigation because of potential danger to the soil or crops. Irrigation water quality can best be determined by chemical laboratory analysis. The main objectives of this study are to assess the surface water quality for irrigation, and to present solutions for managing and protecting these resources in Assiut area. To achieve that, thirty surface water samples were collected from River Nile and main irrigation canals. Chemical analysis was carried out and analyzed for major and trace elements according to the irrigation water guidelines of (FAO 1985), and (Rowe, et al. 1995), taking into account the spatial variations and the representation of the hydro chemical data. The results show that 97% of surface water samples lie within no restriction on use level and 3% is represent slight to moderate restoration on use according to TDS concentrations. 97 % of surface water samples belongs to (C2-S1) good water for irrigation all crops in all soils and 3 % belongs to (C3 -S1) good water for irrigation all crops in all soils under ordinary and specific condition like adequate drainage and leaching According U.S. salinity laboratory staff classification depend on (EC, TDS and SAR). Where 87% Excellent water for irrigation sensitive all crops and low likelihood of soil problems According Boron content. Consequently, it is recommended to prevent the sewage and domestic waste water, and the industrial waste water from direct disposal without treatment to the irrigation canals and River Nile; controlling the use of fertilizers and pesticides in the agriculture purposes; selected the suitable crops for every sector (area) according to the chemical characters of the available irrigation water and soil properties.